2024
DOI: 10.3390/ma17020404
|View full text |Cite
|
Sign up to set email alerts
|

Mycelium-Based Composites as a Sustainable Solution for Waste Management and Circular Economy

Daniel-Gabriel Barta,
Irina Simion,
Ancuța-Elena Tiuc
et al.

Abstract: The global population is expected to increase by nearly 2 billion individuals over the next three decades, leading to a significant surge in waste generation and environmental challenges. To mitigate these challenges, there is a need to develop sustainable solutions that can effectively manage waste generation and promote a circular economy. Mycelium-based composites (MBCs) are being developed for various applications, including packaging, architectural designs, sound absorption, and insulation. MBCs are made … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…The selection of fungal species is a critical factor in the production of MBCs and significantly influences the properties and applications of the final product [ 11 , 24 ]. Currently, many research studies on MBCs have reported numerous fungal species with the potential to produce high-quality MBCs, each exhibiting varying characteristics.…”
Section: Fungal Species Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…The selection of fungal species is a critical factor in the production of MBCs and significantly influences the properties and applications of the final product [ 11 , 24 ]. Currently, many research studies on MBCs have reported numerous fungal species with the potential to produce high-quality MBCs, each exhibiting varying characteristics.…”
Section: Fungal Species Selectionmentioning
confidence: 99%
“…Light exposure: During the colonization phase, mycelium thrives in darkness. Limit exposure to light during this stage [ 11 ].…”
Section: Factors Controlling Production For Mbcsmentioning
confidence: 99%
See 1 more Smart Citation